ART OF BOIKIVSHCHYNA: REVITALIZATION IN A MODERN CONTEXT - Pisio С.; Dudiak Н.; Marusiak В. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
The revitalization of Boikivshchyna art is not only about preserving its authenticity but also about integrating it into new cultural and social realities. This article explores the revitalization process of Boikivshchyna art as part of preserving and enhancing material cultural heritage amid modern architectural and artistic transformations. Revitalization is viewed as a cultural mechanism that not only preserves traditional forms and symbols of folk art but also infuses them with new content and functional meaning within a contemporary social context. The authors highlight the importance of establishing a stable connection between historically developed cultural traditions and new practices in spatial and artistic solutions. The specifics of Boikivshchyna art, along with its rich figurative and semantic structure, are analyzed. The authors outline how local identity can be preserved and transformed through national motifs and by employing contemporary artistic and architectural approaches. By considering these aspects, not only is the aesthetic value of the space enhanced, but the development of the community is also supported, fostering a sense of belonging among its members. Moreover, art can emerge from a thorough analysis of the historical and cultural heritage of a specific location. The article places particular emphasis on the role of local communities, independent artistic initiatives, and cultural institutions that help sustain and rethink cultural heritage. It is determined that through art - as a visual, communicative, and symbolic language - cultural continuity and a reevaluation of national identity are established in the context of globalization. The conclusion drawn is that revitalizing the art of Boikivshchyna paves the way for developing a distinct architectural and environmental design style that harmoniously blends tradition and innovation, especially in rural settlements.